Safety and reliability of blowout preventer using fault tree and event tree analysis - Chua, Darence Kok Zhen (2015)
As the world begins to search and explode new places to extract fuels, there are challenges that follow along. One of the problems encountered is having a blowout. Blowout, which is the uncontrolled released of fuels the environment after pressure control systems have failed, posed tremendous damage to the surroundings. In order to avert such incidents, Blowout Preventers are employed. But still, even with the use of Blowout Preventers, blowouts are still occurring in the world as it is not foolproof. . In order to get a better understanding of the risk and implications involved despite the usage of Blowout Preventer, this project is carried out to quantify the amount of risk based on its probability and consequence from several notable blowouts that had happened. One of it is the Deepwater Horizon which is the largest oil spill to date. For this project, Fault-Tree analysis was carried out to identify and quantify how likely the Blowout Preventer is going to fail. But despite that, knowing just the failure rate is not enough. The economic damage caused by the blowout must be taken into account together with the failure rate so that the actual risk can be understood. This is done so using the Event-Tree analysis and a graph is plotted afterwards so that a clear and simple graphical illustration is available.